Studi Instalasi Listrik pada Gedung Sekolah Budi Bakti Samarinda - Qomaruddin; Arbain; Muhamad Ardyansyah (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study was conducted to evaluate the quality of the electrical installation at Budi Bakti School Building in Samarinda by emphasizing aspects of reliability, safety, energy efficiency, and compliance with applicable electrical installation standards. The research approach involved field surveys to obtain empirical data, measurements of lighting intensity, calculations of the required number of lighting points according to the function and characteristics of each room, as well as technical analysis of installation components, including conductors and protection systems. All observed data were compared with theoretical calculations to identify the level of conformity as well as potential deviations that could cause problems. The findings indicate that although the electrical installation remains operational, there are significant discrepancies, particularly in the distribution of lighting intensity, the number of lighting points, and the selection and placement of protective components that do not fully meet the standards. These discrepancies affect the optimality of lighting, reduce user comfort, and present potential safety risks. Therefore, this study recommends adjustments to the installation design, prioritizing the optimization of the lighting system, the use of standard-compliant components, and the implementation of energy efficiency principles as part of a comprehensive improvement effort. The implications of these findings highlight that regular evaluations and updates of electrical installations in educational buildings are essential to create a safe, comfortable, and productive learning environment. Thus, the results of this research not only provide practical contributions for school management but also offer a scientific basis for developing technical standards of electrical installations that are more responsive to educational needs.